Solar Energy Potential In Regulating Pond Hydroelectric Power Plant Renun Using Helioscope - Muchtar, Gatot Mochamad; Hutabarat, Purnama Helena (Departemen Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2024)
The availability of fossil fuels is increasingly depleting and environmental problems resulting from burning fossil fuels have an impact on environmental problems in the global region, so that efforts are needed to promote alternative energy sources called renewable energy. The Renun Hydroelectric Power Plant (PLTA) is one of the power plants located in Sidikalang which is very suitable for use as a Solar Power Plant (PLTS) which is located in a very large pool and because the Control Pool does not require excavation. for installation and more stable. By using the Helioscope software, the results were obtained in the form of solar panels used in floating PLTS on a pound controller totaling 20,441 solar panels with a Polycristaline model with a power of 300 Wp with the Blue Sun Solar Energy BSM270-300P-60 (300W) type, with the resulting power being 6.12 MWp , The batteries in the PLTS consist of 275 series and 3.5 parallel units so that the total battery required is 1,100 JYC batteries type OPzV3000, and 9 ABB brand inverters type PVI 500 TL CN with a power of 560 kW with a voltage of 360 and the value obtained is the calculation using BMKG data is 308,177 kWh while using Helioscope Software is 489,659 kWh for monthly.